Exploring the relationship between opium consumption and lipid profiles: A population-based study of 10,663 individuals in Southern Iran - Najibullah Baeradeh; Seyed Vahid Hosseini; Leila Moftakhar; Fatemeh Jafari; Masoumeh Ghoddusi Johari; Abbas Rezaianzadeh (Clinical Epidemiology and Global Health)
Background: Drug abuse is known as one of the most important health, medical, and social problems. Furthermore, this study was performed to evaluate the relationship between opium and lipid profiles. Methods: This cross-sectional study was conducted on 10,663 individuals from Kharameh cohort study. Demographic information, and histories of opium, alcohol, and cigarette use were collected by trained staff. Linear regression was employed to examine relationship between opium use and lipid profile. Significance level was considered 5 %, and STATA software was used for analysis. Result: Participants had an average age of 52.2 ± 8.22 years, and 5944 (55.7 %) of them were women. Prevalence of opium use was 16 %. Correlation test indicated that triglyceride showed a significant correlation with age (r = −0.02, P = 0.029), BMI (r = 0.011, P < 0.001), and physical activity (r = −0.45, P < 0.001). Cholesterol were correlated with BMI (r = −0.06, P < 0.001) and physical activity (r = −0.02, P = 0.002). LDL demonstrated correlation with BMI (r = 0.06, P = 0.0001) and physical activity (r = −0.034, P = 0.003), while HDL showed correlation with age (r = 0.062, P < 0.001), BMI (r = 0.061, P < 0.001), and physical activity (r = −0.017, P < 0.001). However, multiple linear regression indicated there was no significant relationship between opium use and lipid profiles (P > 0.05). Conclusion: Our results can help prevent the perception in general population that opium intake lowers lipid levels. Because in our study there was no relationship between opium intake and lipid profile.